Use the definition of derivatives to show that if `f(x)=2x^2+x` ==>`f'(x) = 4x+1`

Expert Answers

An illustration of the letter 'A' in a speech bubbles

`f(x)= 2x^2 + x`

We need to use the definition to show that `f'(x)= 4x+1`

`==gt f'(x)= lim_(h->0)(f(x+h)- f(x))/h `

`==gt f'(x)= lim_(h->0) (2(x+h)^2 + x+h - 2x^2 -x)/h `

`==gt f'(x)= lim_(h->0) (2(x^2+2xh+h^2) +x+h-2x^2 -x)/h `

`==gt f'(x)= lim_(h->0) (2x^2+4xh+2h^2 +x+h-2x^2 -x)/h `

`==gt f'(x)= lim_(h->0) (2h^2 +4xh+h)/h `

`==gt f'(x)= lim_(h->0) (h(2h+4x+1))/h `

`==gt f'(x)= lim_(h->0) (2h+4x+1) = 4x+1 `

`==gt f'(x)= 4x+1`

Approved by eNotes Editorial Team